2018
DOI: 10.14336/ad.2017.0309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elastic Therapeutic Taping on Knee Osteoarthritis: A Systematic Review and Meta-analysis

Abstract: Elastic therapeutic taping (ET) has been widely used for a series of musculoskeletal diseases in recent years. However, there remains clinical uncertainty over its efficiency for knee osteoarthritis (knee OA) management. To assess the effects of ET on patients with knee OA, we investigated outcomes including self-reported pain, knee flexibility, knee-related health status, adverse events, muscle strength, and proprioceptive sensibility. Ten databases including PubMed, EMBASE, Cochrane Library, CINAHL, Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
0
22
0
3
Order By: Relevance
“…It is suggested that it has an effect of localized improvement of blood and lymph flow, decreasing pain, providing anatomical support, enhancing muscle activity and range of motion of joint, and assisting proprioception [10]. However, the standardized skills of application and elastic tension have not been identified yet [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that it has an effect of localized improvement of blood and lymph flow, decreasing pain, providing anatomical support, enhancing muscle activity and range of motion of joint, and assisting proprioception [10]. However, the standardized skills of application and elastic tension have not been identified yet [15].…”
Section: Discussionmentioning
confidence: 99%
“…The standardized application technique and tension have not been identified yet. The systemic review and meta-analysis of KT on OA knee concluded that there is insufficient evidence of KT in treating OA knee and more studies are still needed [15]. Therefore, the aim of this study is to test the effectiveness of KT when used in conjunction with conventional exercise in older OA knee patient.…”
Section: Introductionmentioning
confidence: 99%
“…Sham bandın ise özellikle ağrı ve Alt Ekstremite Fonksiyonel Ölçeği sonuçlarına olumlu katkı sağladığı gözlendi. Osteoartritli olan hastalara uygulanan kinezyobandın; ağrıyı, enflamasyonu ve efüzyonu azalttığı, kas spazmını çözdüğü, diz stabilizasyonunda, eklem hareketinde ve yük dağılımında önemli görevleri olan uyluk kas kuvvetini arttırdığı düşünülmektedir (5,11,17). Kinezyobandın ağrıyı azaltma etkisini; nöro--müsküler yolaklardaki afferent geri bildirimi arttırıp kapı kontrol mekanizmasını işleve koyarak, infrapatellar yağ yastıkçığının enflamasyonunda azalma yaparak, ya da patellanın dizilim bozukluklarını düzeltip uygun yük dağılımını tekrar sağlayarak oluşturduğu öne sürülmektedir (17).…”
Section: Discussionunclassified
“…(5,10). Literatürde kinezyobant etkinliğine ilişkin çalışmalar incelendiğinde, araştırma sonuçlarının bazıları kinezyobandın ağrı, eklem hareket açıklığı, kas kuvveti üzerine etkili olduğunu desteklerken, diğerleri aksi görüş bildirmektedir (4,11). Kinezyobandın osteoartriti olanlarda olumlu veya olumsuz etkisi net olarak ortaya konamamasının yanı sıra, alt ekstremite işlevlerine olan etkisi de yeterince araştırılmamıştır.…”
Section: Introductionunclassified
“…A well-designed RCT is needed to evaluate the effects of elastic taping on pain, disability and sub-maximal exercise performance, especially in combination with exercise. 21 At present, there are no RCT studies of the effects of Mulligan joint mobilization during 24 supervised exercise sessions. There are also few high-quality methodological studies investigating the effects of Mulligan mobilization on the management of KOA; especially the 6-minute walk test (walking di culty), pain and disability.…”
Section: Introductionmentioning
confidence: 99%